Palmito (Bactris gasipaes H.B.K.) growth and management in the humid lowlands of the atlantic zone of Costa Rica - Jongschaap, R. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
Fig. Tab. 13 ref. Sum. (De, En, Es). También como: Field Report - Atlantic Zone Programme (CATIE-AUW-MAG) no. 107